Radiation-induced cellular plasticity primes glioblastoma for forskolin-mediated differentiation - Ling He; Daria Azizad; Kruttika Bhat; Angeliki Ioannidis; Carter J. Hoffmann; Evelyn Arambula; Mansoureh Eghbali; Aparna Bhaduri; Harley I. Kornblum; Frank Pajonk (Proceedings of the National Academy of Sciences, 2025)
Glioblastoma (GBM) is the deadliest brain cancer in adults, and all patients succumb to the tumor. While surgery followed by chemoradiotherapy delays disease progression, these treatments do not lead to tumor control, and targeted therapies or biologics have failed to further improve survival. Utilizing a transient radiation-induced state of multipotency, we used the adenylcyclase activator forskolin to alter the fate of irradiated glioma cells. The effects of the combined treatment on neuronal marker expression, cell cycle distribution, and proliferation were studied. Gene expression profiling was conducted using bulk RNA-seq. Changes in cell populations were investigated using single-cell RNA-seq. Effects on glioma stem cells (GSCs) were studied in extreme limiting dilution assays, and the effects on median survival were studied in both syngeneic and PDOX mouse models of GBM. The combined treatment induced the expression of neuronal markers in glioma cells, reduced proliferation, and led to a distinct gene expression profile. scRNA-seq revealed that the combined treatment forced glioma cells into a microglia- and neuron-like phenotype. In vivo, this treatment led to a loss of GSCs and prolonged median survival. Collectively, our data suggest that revisiting a differentiation therapy with forskolin in combination with radiation could lead to clinical benefit.